Penggunaan media baamboozle untuk meningkatkan keaktifan siswa dalam pembelajaran bahasa arab di sma mamba’us sholihin, sanankulon, blitar - Navisah, Dewi (Maliki Interdisciplinary Journal, 2025)
This study aims to improve student engagement in Arabic language learning through the use of the interactive media Baamboozle. The research was conducted as Classroom Action Research (CAR) with a qualitative approach in class XI B of SMA Mambaus Sholihin, involving 27 students. The research was carried out in two cycles, each consisting of planning, action, observation, and reflection stages. The results showed a significant improvement in student engagement. In cycle I, 55% of students actively answered questions, 60% showed enthusiasm, and 50% were involved in group discussions. After improvements were made in cycle II, student engagement increased to 80% active in answering, 85% enthusiastic, and 75% active in discussions. It can be concluded that Baamboozle is effective in enhancing student participation in Arabic lessons and contributes to a more interactive, engaging, and enjoyable classroom atmosphere.